2023
DOI: 10.1021/jacs.3c01497
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of Early-Stage Quantitative N2 Electrophilic Functionalization

Abstract: Electrophilic functionalization of N2 moieties in metal dinitrogen complexes typically initiates the catalytic synthesis of N-containing molecules directly from N2. Despite intensive research in the last six decades, how to efficiently and even quantitatively convert N2 into diazenido and hydrazido species still poses a great challenge. In this regard, systematic and comprehensive investigations to elucidate the reaction intricacies are of profound significance. Herein, we report a kinetic dissection on the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…This prompted us to use low-temperature fast UV–vis spectroscopy to systematically investigate the electrophilic functionalization reactions of Cr(0)–N 2 complexes (Scheme ). The existence of isosbestic points on the UV–visible spectra could clearly show that the stepwise protonation, alkylation, and silylation reactions with HOTf, MeOTf, and Me 3 SiOTf in each step were quantitative conversions at low temperatures . As shown in Figure , upon treatment with one equivalent MeOTf with 20b in a 2-MeTHF solution at 153 K, an isosbestic point at 620 nm was observed, indicative of the quantitative formation of Cr­(II)–NN–Me ( 21-Me ).…”
Section: Chromium Dinitrogen Complexes Bearing Cyclopentadienyl and B...mentioning
confidence: 92%
See 2 more Smart Citations
“…This prompted us to use low-temperature fast UV–vis spectroscopy to systematically investigate the electrophilic functionalization reactions of Cr(0)–N 2 complexes (Scheme ). The existence of isosbestic points on the UV–visible spectra could clearly show that the stepwise protonation, alkylation, and silylation reactions with HOTf, MeOTf, and Me 3 SiOTf in each step were quantitative conversions at low temperatures . As shown in Figure , upon treatment with one equivalent MeOTf with 20b in a 2-MeTHF solution at 153 K, an isosbestic point at 620 nm was observed, indicative of the quantitative formation of Cr­(II)–NN–Me ( 21-Me ).…”
Section: Chromium Dinitrogen Complexes Bearing Cyclopentadienyl and B...mentioning
confidence: 92%
“…In order to achieve more efficient functionalization reactions, we replaced the monophosphine and monocarbene ligands with a simple bisphosphine ligand and synthesized the corresponding dinuclear Cr­(I)–N 2 complex 19 and mononuclear Cr(0)–N 2 complex 20 (Scheme ). The magnetometric study of precursor Cr­(II) chloride 18 revealed its S = 1 ground state. Compared with the monophosphine and monocarbene analogues, the reduction extent of N 2 units is stronger in both 19 and 20 , as evidenced by the longer N–N bond lengths and lower N–N bond-stretching vibrational frequencies.…”
Section: Chromium Dinitrogen Complexes Bearing Cyclopentadienyl and B...mentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Quite recently, Xi and coworkers reported the stepwise functionalization of N 2 ligand on an anionic chromium complex bearing Cp* ligand K[Cp*Cr(depe)N 2 ] (Cp* = η 5 -C 5 Me 5 , depe = 1,2-bis(diethylphosphino)ethane) with MeOTf to give a cationic dimethyl hydrazide complex [Cp*Cr(depe)(= NNMe 2 )]OTf via a monomethyl diazenide complex [Cp*Cr(depe)(N=NMe)]. [28] In contrast to the addition of carbon-centered electrophiles to terminal N 2 ligand, Sellman and coworkers reported the reaction of a manganese-N 2 complex bearing a Cp ligand [Cp(CO) 2 Mn(N 2 )] (Cp = η 5 -C 5 H 5 ) with phenyl lithium (PhLi) as a carbon-centered nucleophile to form the anionic diazenide complex Li[Cp(CO) 2 Mn(NPh=N)]. [29] However, a recent study showed that the proposed reaction is unlikely to occur, and suggested that PhLi reacts with one of the CO ligands to provide an anionic acylcarbonyl dinitrogen complex Li[Cp-(CO)(N 2 )MnCOPh], then it decomposed to give an anionic phenyl complex Li[Cp(CO) 2 MnPh], which was misassigned in the original literature as the anionic diazenide complex with nitrogen-carbon bond.…”
Section: Stoichiometric Formation Of Nitrogen-carbon Bonds On Dinitro...mentioning
confidence: 99%
“…[ 10‐13 ] Hence, a variety of strategies have been developed to achieve dinitrogen reduction more efficiently and in an environmentally‐friendly manner. [ 14‐37 ]…”
Section: Introductionmentioning
confidence: 99%